Effect of sparger design on the flow in a bubble column: symbolic analysis of LDA data - Kulkarni, A. A.; Deshpande, Suvarna S.; Joshi, J. B.; Kumar, V. Ravi; Kulkarni, B. D. (Industrial & Engineering Chemistry Research, 2007)
This paper aims at developing a methodology that helps in the characterization of the effects of a single point and multipoint sparger on the flow patterns in a bubble column reactor. The methodology uses the simultaneously measured instantaneous velocity-time data (two orthogonal velocity components) using LDA at different measurement locations. The data sets are transformed into their equivalent description in terms of polar coordinates, viz., resultant velocity vector and angle. This information is further transformed in terms of symbolic representation in a binary number format. The covariance matrices obtained from the binary data are analyzed for their eigenvalues, and the spectrum is used for the identification of the dominant, energy containing modes in the data. In the vicinity of the sparger, the nature of covariance matrix and the eigenvalue spectrum for the single point sparger (SPS) data was significantly different from that of the multipoint sparger (MPS). In the bulk region, for both types of spargers, the nature of the eigenvalues and the number of dominant modes is seen to be different from the near sparger region. In general, more numbers of eigenvalues are required to capture the total energy in the data for a multipoint sparger when compared to a single point sparger. This suggests a higher level of complexities existing due to the intricate hydrodynamics for the multipoint sparger. The possible use of this methodology for practical purposes, e.g., identification of malfunctioning of gas-liquid sparger reactors is discussed.

Exhaustive analysis of frontal copolymerization of functionalized monovinyl and divinyl monomers - Pujari, Narahari S.; Inamdar, Satish R.; Ambekar, Jalindar D.; Kulkarni, B. D.; Ponrathnam, Surendra (Chemistry-A European Journal, 2007)
A series of copolymers of 2-hydroxyethyl methacrylate (HEMA)/ glycidyl methacrylate (GMA) and ethylene dimethacrylate (EGDM) were synthesized by frontal polymerization (FP). This study was conducted to investigate the effect of crosslink density, type and concentration of initiator, the use of a complex initiator system, porogen, and diluent on the most relevant parameters of FP, such as sustainability of the front, temperature profile, front velocity, and yield. The products were also characterized for intruded pore volume, pore-size distribution, epoxy-functionality number, and surface morphology. Higher crosslink densities (CLDs) and initiator concentration produced higher front velocities, whereas no trend in front temperature was noted. A complex initiation system was effective in stabilizing and increasing the polymerization yield. Relative to suspension polymerization (SP), FP products synthesized without a solvent were microporous, whereas micro-to-macroporous products were obtained in the presence of a solvent (for HEMA-EGDM polymers). We also present, explain, and discuss the exotic patterns observed under a microscope. We observed two basic types of spatial patterns, namely, planar and nonplanar patterns. The type of planar pattern observed under scanning electron microscopy (SEM) has a spatial impulse that appears as a loop followed by regular periodic motion in the radial and axial directions. This behavior gives rise to a repeating pattern that is a few microns thick. Also, nonplanar patterns, namely, layered concentric rings and winding staircase patterns, were observed under SEM.
Keywords: copolymerization; patterns; Polymers; porosity

Evaluation of repulsive particle swarm method for phase equilibrium and phase stability problems - Rahman, Imran; Das, Anwesh Kr.; Mankar, Raju B.; Kulkarni, B. D. (Fluid Phase Equilibria, 2009)
Phase equilibrium and stability problems are of crucial importance in simulation, design and optimization of several separation processes. Recently, these problems have been solved using minimization of Gibbs free energy, using global optimization techniques. In this paper, repulsive particle swarm (RPS), a recent global optimization technique is explored for the Solution of phase stability and phase equilibrium. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Liquid-liquid equilibria; Phase equilibrium; Phase stability analysis; Repulsive particle swarm method

Embedded multiple shooting methodology in a genetic algorithm framework for parameter estimation and state identification of complex systems - Sarode, Ketan Dinkar; Kumar, V. Ravi; Kulkarni, B. D. (Chemical Engineering Science, 2015)
A novel parameter estimation and state identification algorithm for nonlinear dynamical systems from data by embedding a multiple shooting methodology in the framework of a genetic algorithm (EMSGA) is described. The advantages of EMSGA are brought out by studies with two highly nonlinear examples, viz., the chaotic dynamics of a non-isothermal CSTR and the glycolysis regulation in Lactococcus lactis for production of lactic acid. For the chaotic dynamics with extremely high sensitivity to parameter values and initial conditions, EMSGA accurately estimates all process parameters while at the same time recovering the true dynamics of monitored and unmonitored variables from limited extents of noisy dynamic data. The superiority in accuracy and computational time of EMSGA over standalone genetic or multiple shooting algorithms for parameter estimation is shown for comparison purposes. In fact, EMSGA adapts well to the use of generalized canonical models, e.g., the S-system, where use of the fundamental Taylor series method of any order for integration becomes possible. This makes EMSGA highly efficient and exemplified here by estimating all the parameters of the derived higher dimensional 5-system model for the CSTR. Comparative studies with a well-known global-local enhanced scatter search method corroborate the suitability and advantages of the EMSGA methodology. For the glycolysis regulation example the numerical robustness of EMSGA is brought out by estimating a large number of model parameters when a majority of them are raised to the power of the state variables. Interestingly, we show that from noisy in vivo dynamic data it becomes possible to completely recover the noise-free dynamical behavior of unmonitored species concentrations using EMSGA. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Canonical models; Chaotic dynamics; Genetic algorithm; Multiple shooting; Noise reduction; parameter estimation

Effect of different temperature on structural, magnetic and dielectric properties of strontium hexaferrite powder synthesised using aloe vera plant extracts - Solanki, Neha; Jotania, R. B.; Khomane, Ramdas B.; Kulkarni, B. D. (Advanced Science Letters, 2016)
M-type SrFe12O19 hexaferrite particles synthesized using the aloe vera plant extract. Biological materials of microorganisms, plants, enzymes have been suggested as an ecological alternative for conventional reagents in physical and chemical methods. In present paper we report effect of temperature on structural, morphology, magnetic and dielectric properties of M-type SrFe12O19 particles synthesised by Green synthesis technique using Aloe vera plant extract. The metal nitrates (Sr and Fe) were dissolved in aloe vera extract solution and then mixture was kept in oil bath at 100 degrees C till it become dry. The obtain dried powder calcined in a wide temperature range, from 450 degrees C to 1150 degrees C for 4 hours in a static air atmosphere. The calcined powders were characterised using various instrumental techniques like Fourier transform infrared spectroscopy (FTIR) X-ray diffractometry (XRD), Scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), Vibrating Sample Magnetometry (VSM), and dielectric measurements. XRD, FTIR, SEM, Magnetic and dielectric measurements were carried out at room temperature. XRD analysis confirms the formation of mono phase of strontium hexaferrite at 1150 degrees C.
Keywords: Aloe Vera Extract; green synthesis; M-Type Hexaferrite; Strontium Hexaferrite